(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with peculiarities of synonymic relations in military lexics after the example of names of weapons, accoutrements and military installations. The problem of manifestation of synonymy in military lexics is analyzed.